Anti-platelet therapy is efficacious in treating endometriosis induced in mouse. Issue 4 (October 2016) - Guo, Sun-Wei; Ding, Ding; Liu, Xishi
Highlights: Ozagrel treatment led to reduced lesion size in mice with induced endometriosis. It resulted in reduced expression of markers of proliferation and angiogenesis It also reduced the expression of markers of fibrosis Both pre-emptive and after-induction platelet depletion achieved similar effects Sequential depletion of platelets and macrophages also achieved similar effects Abstract: In light of recent findings showing that platelets play important roles in the development of endometriosis in general and in fibrogenesis in particular, this study investigated the efficacy of Ozagrel, a TXA2 synthase inhibitor, in a murine model of endometriosis. In addition, another mouse experiment was conducted to evaluate the effect of timing of platelet depletion and of sequential depletion of platelets and macrophages on the development of endometriosis. It was found that both the Ozagrel treatment and different platelet depletion schemes resulted in significant reduction in lesion growth (all P -values <0.01) along with improved hyperalgesia in mice with induced endometriosis. They also significantly reduced the expression of markers of proliferation, angiogenesis, inflammation and fibrosis as well as decreased macrophage infiltration in endometriotic lesions (all P -values <0.05). Compared with untreated mice, pre-emptive depletion of platelets as well as platelet depletion after induction resulted in significant reduction in lesion weight (both P -values <0.001), while sequential depletion of platelets and macrophages yielded similar reduction. These results, in conjunction with other roles that platelets play in the development of endometriosis, strongly argue for the potential of anti-platelet therapy in treating endometriosis.